Much to Do About Trauma: A Systematic Review of Existing Trauma-Informed Treatments on Youth Violence and Recidivism - Zettler, Haley R. (Youth violence and juvenile justice, 2021)
Research has demonstrated a relationship between childhood trauma, violence, and justice involvement. As juvenile justice systems have become more attune to the needs of traumatized youth, a number of trauma-informed treatment programs have been developed to mitigate the effects of trauma. Evaluations of trauma-informed treatment demonstrate their effectiveness in reducing trauma-related symptoms. Further, prior research has found that trauma-informed treatment can reduce behavioral infractions and institutional violence. While there is indirect evidence that trauma-informed treatment reduces juvenile violence and recidivism, no research to date has assessed trauma-informed treatment on behavioral outcomes outside of residential facilities. This systematic review provides an overview of the use trauma-informed treatment in juvenile justice settings and provides recommendations for practice and future research.